2021
DOI: 10.1186/s40621-021-00310-4
|View full text |Cite
|
Sign up to set email alerts
|

The Advancing Understanding of Transportation Options (AUTO) study: design and methods of a multi-center study of decision aid for older drivers

Abstract: Background Decision-making about when to stop driving for older adults involves assessment of driving risk, availability of support or resources, and strong emotions about loss of independence. Although the risk of being involved in a fatal crash increases with age, driving cessation can negatively impact an older adult’s health and well-being. Decision aids can enhance the decision-making process by increasing knowledge of the risks and benefits of driving cessation and improve decision qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 40 publications
(40 reference statements)
0
10
0
Order By: Relevance
“…Participants were enrolled in the AUTO study, a randomized trial of older drivers and simultaneously enrolled study partners (family member or friend) with longitudinal follow-up at 6, 12, 18 and 24 months. As described elsewhere in detail (Betz et al, 2021), eligible participants were adults aged ≥70 years who spoke English, drove at least once a week with a valid license, had a primary care provider affiliated with one of the study sites (San Diego, California; Denver, Colorado; Indianapolis, and Indiana), and had at least one medical condition known to be associated with impaired driving safety or increased likelihood of driving cessation. Study staff identified potentially eligible individuals from primary care clinic rosters and then contacted them via letter and telephone.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were enrolled in the AUTO study, a randomized trial of older drivers and simultaneously enrolled study partners (family member or friend) with longitudinal follow-up at 6, 12, 18 and 24 months. As described elsewhere in detail (Betz et al, 2021), eligible participants were adults aged ≥70 years who spoke English, drove at least once a week with a valid license, had a primary care provider affiliated with one of the study sites (San Diego, California; Denver, Colorado; Indianapolis, and Indiana), and had at least one medical condition known to be associated with impaired driving safety or increased likelihood of driving cessation. Study staff identified potentially eligible individuals from primary care clinic rosters and then contacted them via letter and telephone.…”
Section: Methodsmentioning
confidence: 99%
“…Study recruitment began in December 2019 and continued through June 2021; there was a pause in recruitment from March 12 to May 18, 2020 as the staff adjusted study protocols for remote enrollment and inclusion of COVID-19–related measures. Participants will have continued follow-up at pre-determined intervals for 24 months (Betz et al, 2021); the current analysis includes only baseline data from older drivers (referred to hereafter as “participants”), not study partners. All participants provided informed consent, and the study was approved by the institutional review boards of University of California San Diego, University of Colorado, and Indiana University.…”
Section: Methodsmentioning
confidence: 99%
“…AUTO is a randomized, controlled trial of older drivers, with methods described in detail elsewhere 20 . The trial was designed to assess the effect of the Healthwise® DDA 18 on immediate outcomes (as reported here) and over 2 years of longitudinal follow‐up.…”
Section: Methodsmentioning
confidence: 99%
“…Additional eligibility criteria for older adults included: receiving primary care through healthcare systems in San Diego, California, Denver, Colorado, Indianapolis, or Indiana; being fluent in English (as DDA is only available in English); being able and willing to complete telephone follow‐up calls; driving at least weekly with a valid driver's license; reporting no major changes to health, vision, or hearing that seriously impair driving since last license renewal; and not feeling the DMV would have serious concerns about driving. Because the study examines decision‐making about driving cessation, older adults had to have at least one electronic health record (EHR) diagnosis of a progressive condition associated with reduced driving ability and increased risk of cessation (as defined by the study team; examples include macular degeneration, diabetic retinopathy, congestive heart failure, Parkinson disease, vertigo, arthritis and foot abnormalities, and sleep apnea) 20 . Individuals were ineligible if they were already enrolled in the LongROAD study (a longitudinal observational study of older drivers), 25 were in legal custody or institutionalized, or had a 5‐min Montreal Cognitive Assessment (MoCA) score < 21.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation